Impact of Pharmacist-Led Training on Breast Cancer Awareness and Knowledge: A Quasi-Experimental Pre-Post Study - Yılmaz, Zekiye; Eliçetin, Ceren (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Breast Cancer (BC) constitutes the primary cause of cancer-related mortality in females and BC burden is projected to rise to 3.19 million cases and 1.04 million deaths by 2040. Given the increasing prevalence of BC, all healthcare professionals, including pharmacists, are responsible for raising women's Awareness and Knowledge (AAK) of BC and its prevention. The aim of this research was to assess the impact of pharmacist-led training on women's AAK of BC, as well as to evaluate their willingness to receive such training from pharmacist. Materials and Methods: This was a quasi-experimental pre-post study conducted in a community pharmacy in Bursa, Türkiye, using a structured, validated questionnaire to assess women's breast cancer AAK and evaluate the impact of pharmacist-led training. The questionnaire was administered face-to-face at baseline and one month following the training. Results: 263 women included in the study. The mean age of the participants was 38.76±11.42. 36.9% of participants had one risk factor for BC. 83.3% of the participants had no training before. Regardless of sociodemographic characteristics, all of the participants’ AAK increased significantly post-training (p=0.00) and the mean overall breast cancer awareness scale score was increased from 76.70±7.71 to 87.43±5.11. Conclusion: There exists a deficiency in AAK regarding BC among Turkish women, specifically concerning risk factors, signs and symptoms, attitudes toward prevention and methods for breast screening. Therefore, the substantial role of pharmacist in enhancing women's AAK presents a promising development. Although this study was conducted within a limited time frame and in a single pharmacy and has limitations such as the lack of long-term follow-up, it can be considered a complementary strategy to raise breast cancer AAK in the community due to its significant contributions.
Keywords: Breast cancer; Knowledge and awareness; Pharmacist; B-cas; Early diagnosis; Training